First record of the Nearctic leafhopper Erasmoneura vulnerata (Fitch, 1851) Hemiptera, Cicadomorpha: Cicadellidae in Slovenia - Seljak, Gabrijel (Acta entomologica slovenica (Ljubljana), 2011)
In autumn 2010 the first findings of the North American leafhopper Erasmoneuravulnerata (Fitch, 1851) were recorded in Slovenia. Fairly large populations were observed in various localities around Nova Gorica especially on Vitis labrusca 'Isabella' and Cercis siliquastrum. Short description of thespecies and its biology are given.
Keywords: entomologija; entomology; Erasmoneura vulnerata; fauna; favna; grapevine pest; Slovenia; Slovenija; škodljivci; Typhlocybinae; vinska trta